Mobile apps for treatment of speech disorders in children: An evidence-based analysis of quality and efficacy - Furlong, Lisa (PLoS One, 2018)
BACKGROUND: Recently there has been exponential growth in mobile health (mHealth) applications (apps) for children with speech disorders. A challenge for health professionals and families is knowing how to find high quality apps that are therapeutically beneficial. We systematically search and critique the quality of mobile apps for childhood speech disorders. An evidence-based method for identifying suitable apps in the Google Play and Apple iTunes stores is also proposed. METHODS AND FINDINGS: A systematic search of the Google Play and Apple iTunes app stores was conducted from November 2016 to May 2017. Twelve pre-defined search terms were applied, identifying 5076 apps. Systematic screening resulted in 132 unique apps for full appraisal. These were appraised by two raters using the Mobile Application Rating scale. None were of excellent quality. Twenty-five were of good quality, 105 average and 2 were poor or very poor. DISCUSSION: It can be challenging for consumers to locate high quality speech therapy apps for children. Although we found more than 5000 apps, less than 3% met criteria for evaluation. Difficulties sourcing valid apps included: (i) Boolean operators were not available and therefore only one search term could be used each time (ii) the order of app listings in online stores continually changed (iii) apps were organised in online stores according to relevance and popularity (iv) there was no easy way to extract app titles and eliminate duplicates (v) app cost did not always correlate with therapeutic quality. CONCLUSIONS: The rapid growth of mHealth heightens the need to develop rigorous and efficient systems to search and retrieve apps and evaluate their therapeutic benefits. Given the difficulty accessing speech therapy services worldwide, mHealth promises therapy benefits when apps are reliable, valid and easily found.